Potential economic impacts from improving breastfeeding rates in the UK. Issue 4 (4th December 2014) - Pokhrel, S; Quigley, M A; Fox-Rushby, J; McCormick, F; Williams, A; Trueman, P; Dodds, R; Renfrew, M J
Abstract : Rationale: Studies suggest that increased breastfeeding rates can provide substantial financial savings, but the scale of such savings in the UK is not known. Objective: To calculate potential cost savings attributable to increases in breastfeeding rates from the National Health Service perspective. Design and settings: Cost savings focussed on where evidence of health benefit is strongest: reductions in gastrointestinal and lower respiratory tract infections, acute otitis media in infants, necrotising enterocolitis in preterm babies and breast cancer (BC) in women. Savings were estimated using a seven-step framework in which an incidence-based disease model determined the number of cases that could have been avoided if breastfeeding rates were increased. Point estimates of cost savings were subject to a deterministic sensitivity analysis. Results: Treating the four acute diseases in children costs the UK at least £89 million annually. The 2009–2010 value of lifetime costs of treating maternal BC is estimated at £959 million. Supporting mothers who are exclusively breast feeding at 1 week to continue breast feeding until 4 months can be expected to reduce the incidence of three childhood infectious diseases and save at least £11 million annually. Doubling the proportion of mothers currently breast feeding for 7–18 months in their lifetime is likely to reduce the incidence of maternal BC and save at least £31 million at 2009–2010 value. Conclusions: The economic impact of low breastfeeding rates is substantial. Investing in services that support women who want to breast feed for longer is potentially cost saving.